School strictness and disproportionate minority contact: investigating racial and ethnic disparities with the 'school-to-prison pipeline' - “Trey” Marchbanks, Miner P. (Youth violence and juvenile justice, 2018)
There are racial and ethnic disparities associated with school discipline practices and juvenile justice contact. In addition, research suggests that stricter school discipline practices and disproportionate minority contact for minority youth are relatively more prevalent in urban areas. What remains unknown, however, is the relationship between race and ethnicity, school discipline practices, and juvenile justice referrals across urban, rural, and suburban schools. Therefore, this study draws from the Texas Education Agency’s Public Education Information Management System to investigate the relationship between school discipline practices and juvenile justice contact with a focus on racial and ethnic disparities in urban, rural, and suburban schools. Findings indicate that both stringent and lenient school discipline practices have effects on juvenile justice referrals as well as racial and ethnic disparities across distinct school locations; however, there are important and distinctive nuances that are presented and examined.